Imam Hafs b. Sulayman Abu ‘Umar al-Asadi: A Critical Comparative Analysis of his Qur’anic and Hadith Narration - Bensala, Youcef; Bensaid, Benaouda; Abdullah Qasem Al-Nahari, Ameen Ahmed; Gokaru, Shuaibu Umar (Jurnal Usuluddin, 2024)
This research examines the narration of Imam Hafs, whose popularity is widespread among Muslims due to his expertise in the recitation of the Qur’an. Specifically, the paper aims to study the criticism and authenticity of Imam Hafs’ narration, focusing on critiques by scholars such as al-Daraqutni and Yahya ibn Ma‘in, who categorized his narration as weak and unreliable. They argue that he lacked sharp memory, among others deficiencies. The central question addressed in this study is whether whether the statement regarding the weakness of his narration is general or specifically limited to his Hadith narrations, or if it also concerns his Qur’anic recitations on the authority of ‘Asim ibn Abi al-Najud. This study employs a critical comparative method, utilizing analytical, inductive, and comparative approaches in accordance with the science of Hadith criticism (al-Jarh wa al-Ta‘dil) to determine the views of Hadith scholars about Hafs’ narrations in both the Qur’an and Hadith. The views of scholars were collected, reviewed, and comparatively analyzed, with special consideration given to opinions supported by substantial evidence. The study concluded That Imam Hafs is universally recognized as a reliable authority in Quranic recitation. While critiques of his Hadith narration exist, they stem from his primary focus on Quran recitation, leaving limited scope for mastery in Hadith. This does not impact his esteemed status or the widespread adoption of his recitation today, as scholars across disciplines unanimously affirm his reliability in Quranic readings and teaching.